2003
DOI: 10.1128/cdli.10.1.169-173.2003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Safety ofLactobacillusStrains Based on Resistance to Host Innate Defense Mechanisms

Abstract: Seven Lactobacillus strains belonging to four species were evaluated for pathogenicity as well as for in vitro sensitivity to the bactericidal mechanisms of macrophages in a rabbit infective endocarditis (IE) model. Two bacteremia-associated strains, L. rhamnosus PHLS A103/70 and L. casei PHLS A357/84, as well as the L. rhamnosus type strain and the probiotic L. rhamnosus strain ATCC 53103, showed moderate infectivity, and the virulence of the probiotic L. casei strain Shirota and type strains such as L. acido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 23 publications
0
35
1
Order By: Relevance
“…In contrast to the report of Korhonen et al, we found that L. rhamnosus acts antagonistically to IFN-g in NO production by pig alveolar macrophages (Asahara et al, 2003;Erickson & Hubbard, 2000;Korhonen et al, 2001Korhonen et al, , 2002. It may be that the action of lactobacilli and/or bifidobacteria is not only specific to the individual bacterial strain or species but is strongly dependent on the cell type.…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast to the report of Korhonen et al, we found that L. rhamnosus acts antagonistically to IFN-g in NO production by pig alveolar macrophages (Asahara et al, 2003;Erickson & Hubbard, 2000;Korhonen et al, 2001Korhonen et al, , 2002. It may be that the action of lactobacilli and/or bifidobacteria is not only specific to the individual bacterial strain or species but is strongly dependent on the cell type.…”
Section: Discussioncontrasting
confidence: 84%
“…Although several reports of sepsis in at-risk individuals have been linked to lactobacilli, there is no conclusive evidence from analysis of clinical isolates that would indicate any species-related properties that would favor infection in atrisk populations. 14 Asahara and colleagues 137 have suggested that resistance to host innate defence mechanisms should be considered in the safety assessment of Lactobacillus strains, but research in this area is limited.…”
Section: Microbiological and Metabolic Issues Related To Safetymentioning
confidence: 98%
“…With this background in mind it is possible to consider bacteremia due to Lactobacillus as an index of serious defects in the immunity of those affected 3 . In episodes of bacterial endocarditis in adults, Lactobacillus appears as an etiological agent in 0.05 to 0.4% of episodes, reflecting its a limited capacity to adhere to the endothelium of undamaged heart valves, which was confirmed in experimental models 4 . In a study of 280 infants, who received one of three infant formulas containing different probiotics and prebiotics between birth and 4 months of age, there were no negative effects on their growth and development.…”
mentioning
confidence: 69%